2018
DOI: 10.2174/1381612824666181018153641
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ABCB1 Genotypes on the Pharmacokinetics and Clinical Outcomes of New Oral Anticoagulants: A Systematic Review and Meta-analysis

Abstract: Background: New Oral Anticoagulants (NOACs) are effective and widely used to prevent and treat thromboembolic diseases, but the response to NOACs differs according to ABCB1 genotypes. Objective: We investigated the effects of ABCB1 genotypes on the pharmacokinetics and clinical outcomes of NOACs. Methods: We searched PubMed, Embase, and the Cochrane Library for studies on ABCB1 genotypes published from the inception of these databases until May 23, 2018. The Weighted Mean Difference (WMD) and Odds Ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 0 publications
2
20
1
2
Order By: Relevance
“…46) In particular, the effects of ABCB1 C3435T polymorphism on other types of anticoagulants and antiplatelet drugs have been reported. [47][48][49][50] Similar to the results of this study, a meta-analysis that reported a relationship between ABCB1 C3435T polymorphism and treatment response to clopidogrel showed that the ABCB1 3435T allele was associated with a significantly increased incidence rate of bleeding events in the Asian population (OR 1.805, 95% CI 1.124 to 2.900, p=0.015). 49) In addition, the ABCB1 3435T allele was associated with a significantly reduced platelet activity (standardized mean difference with fixed effect model −0.140, 95% CI −0.272 to −0.009, p=0.036).…”
Section: Discussionsupporting
confidence: 83%
“…46) In particular, the effects of ABCB1 C3435T polymorphism on other types of anticoagulants and antiplatelet drugs have been reported. [47][48][49][50] Similar to the results of this study, a meta-analysis that reported a relationship between ABCB1 C3435T polymorphism and treatment response to clopidogrel showed that the ABCB1 3435T allele was associated with a significantly increased incidence rate of bleeding events in the Asian population (OR 1.805, 95% CI 1.124 to 2.900, p=0.015). 49) In addition, the ABCB1 3435T allele was associated with a significantly reduced platelet activity (standardized mean difference with fixed effect model −0.140, 95% CI −0.272 to −0.009, p=0.036).…”
Section: Discussionsupporting
confidence: 83%
“…Both the FDA and CPIC have recommended to consider both the CYP2C9*2, *3 and VKORC1 (rs9934438) genetic variants for optimizing its safety, that is, bleeding or efficacy in order to achieve precision medicine of warfarin (Dean, 2012;Johnson et al, 2017). Other new oral anticoagulants such as debigatran, rivaroxaban, and apixaban are affected by the ABCB1 genetic variants and should be considered clinically for optimizing the safety and efficacy (Xie et al, 2018;Kanuri and Kreutz, 2019).…”
Section: Anticoagulantsmentioning
confidence: 99%
“…The expression of rivaroxaban transporter proteins may be influenced by SNVs of the ABCB1 gene, but information on their clinical significance is inconsistent. The systematic review and meta-analysis by Xie Q. et al (2018) showed that Cmax was lower in carriers of ABCB1 rs1045642 CC than carriers of TT, and carriers of rs2032582 GG than carriers of A/T allele, and AUC0–∞ was lower in rs1045642 CC carriers than in TT carriers [ 48 ]. According to Gouin-Thibault I. et al (2017), ABCB1 polymorphism cannot be considered as a significant determinant of individual variability in pharmacokinetics of rivaroxaban, and combined use of P-gp/CYP3A4 inhibitor clarithromycin with rivaroxaban may require caution in patients at risk of overdose, as it leads to a two-fold increase in AUC genotype ABCB1 [ 26 ].…”
Section: Rivaroxabanmentioning
confidence: 99%